Inflation Control Through Modeling Results of Factors that Affecting Inflation Using Robust Time Series Regression S-Estimation and MM-Estimation (Government and Statistics, 2022)
Inflation is a natural phenomenon in the economy if it is in the light limit, but if it is in the medium or high category it can certainly have a heavy impact on a country's economy, especially in the process of recovering economic activity due to the impact of COVID-19. Peak Inflation in Indonesia in the period of the first time Covid-19 appeared in the world, that is November 2019 to July 2022, it happened in July 2022 by 4,94 percent or almost reaching 5 percent. One of the efforts to control inflation is to find out the factors that affect inflation, therefore this research was conducted with the aim of analyzing factors that are considered to affect inflation in Indonesia. The statistical analysis method used in this research is robust time series regression with estimation of S (Scale) and estimation of MM (Method of Moment). The optimal estimator robust time series regression for model inflation in Indonesia in the period November 2019 to July 2022 is robust time series regression MM-estimation, with the R-square (adjusted) is 93,34%, and it is known that there are 3 variables that have a significant effect on inflation, that are the value of inflation itself in the previous period, the exchange median rates on transaction USD to IDR, and world crude oil prices.
Keywords: inflation; modeling; Robust MM-Estimation; Robust S-Estimation